KAJIAN FENOMENA TAWURAN PELAJAR PENDIDIKAN MENENGAH - Ikhya Ulumudin (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2016)
This study aims to find out factors behind the occurrence of students brawl by analyzing these aspects; family background, school’s environment, and peers, and also to find a school policy alternative to help shaping students’ characters. This study employed qualitative approach. Data and information were collected through interviews. The conclusion is that the factors causing student brawl divided into two types, direct factors and indirect factors. Direct factors are mainly long ongoing dispute that is brought over generations of students between the two sample schools, the location of schools which is adjacent to each other, the habit of going to and from school in groups, and the habit to bully (mock, insult, spit at) one another when passing by on the street. The indirect factor, on the other hand, are family and school. A school policy alternative to cope with students brawl is by enforcing school disciplines, for example through an imposition of punishment and reward and also forming and enforcing teachers’ disciplines at school.